2011
DOI: 10.1063/1.3567415
|View full text |Cite
|
Sign up to set email alerts
|

Chirality and thickness-dependent thermal conductivity of few-layer graphene: A molecular dynamics study

Abstract: The thermal conductivity of graphene nanoribbons (layer from 1 to 8 atomic planes) is investigated by using the nonequilibrium molecular dynamics method. We present that the room-temperature thermal conductivity decays monotonically with the number of the layers in few-layer graphene. The superiority of zigzag graphene in thermal conductivity is only available in high temperature region and disappears in multi-layer case. It is explained that the phonon spectral shrink in high frequency induces the change of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
78
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(95 citation statements)
references
References 22 publications
13
78
1
1
Order By: Relevance
“…The maximum thickness considered in our study is 12 layers, which has a total number of 91,496 atoms including the substrate atoms. With the increase of graphene layers, it exhibits a very rapid enhancement in thermal conductivity of supported FLG at the beginning, followed by a much slower increase after six layers, showing an obvious two-stage increase characteristic which has also been observed in a recent experimental study on the thickness dependent thermal conductivity of encased graphene [29].On the other hand, it has been reported that thermal conductivity of suspended FLG decreases with the thickness due to the inter-layer interactions [30,31]. It is known that both inter-layer interaction and graphene-substrate interaction can lead to the reduction of thermal conductivity in graphene due to damping of the ZA phonons.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…The maximum thickness considered in our study is 12 layers, which has a total number of 91,496 atoms including the substrate atoms. With the increase of graphene layers, it exhibits a very rapid enhancement in thermal conductivity of supported FLG at the beginning, followed by a much slower increase after six layers, showing an obvious two-stage increase characteristic which has also been observed in a recent experimental study on the thickness dependent thermal conductivity of encased graphene [29].On the other hand, it has been reported that thermal conductivity of suspended FLG decreases with the thickness due to the inter-layer interactions [30,31]. It is known that both inter-layer interaction and graphene-substrate interaction can lead to the reduction of thermal conductivity in graphene due to damping of the ZA phonons.…”
mentioning
confidence: 72%
“…On the other hand, it has been reported that thermal conductivity of suspended FLG decreases with the thickness due to the inter-layer interactions [30,31]. It is known that both inter-layer interaction and graphene-substrate interaction can lead to the reduction of thermal conductivity in graphene due to damping of the ZA phonons.…”
mentioning
confidence: 99%
“…7(d)) of single-layer and multi-layer GNRs are also investigated by using MD simulations. 111 Zhai and Jin investigated the strain effect on ballistic thermal transport in GNR by combination of NEGF and the elastic theory. 106 At temperature below 50 K, the thermal conductance increases observably for GNR with stretching strain of 10% and 19%, due to a lot of dispersive phonon modes are converged to the low frequency region.…”
Section: B 2d Nanostructuresmentioning
confidence: 99%
“…There are rich physical phenomena about thermal property of GNRs. The effects of size, [95][96][97][98] defects, 99, 100 doping, 101,102 shape, 103,104 stress/strain,, [105][106][107][108] substrates, 109 inter-layer interactions, [110][111][112] nanoscale junctions, 113 chirality, 114 topological structure, 115 edge effect, [116][117][118][119] foldings (gradfolds), 23,120 etc. on thermal conductivity of nanoribbons [121][122][123][124][125][126][127][128] have been widely studied.…”
Section: B 2d Nanostructuresmentioning
confidence: 99%
“…The Nosé-Hoover thermostats are applied to the left and right end of GNRs [6,7,20]. We integrate the equations of motion for atoms by the Verlet method [21].…”
mentioning
confidence: 99%